2009
DOI: 10.11646/zootaxa.2293.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Pacific lowland snakes of the genus Atractus (Serpentes: Dipsadidae), with description of three new species

Abstract: The taxonomic status of the Pacific lowland Atractus is revised on the basis of meristic, morphometric, colour pattern, and hemipenial characters. Geographical variation is reported for six Atractus species (A. boulengerii, A. clarki, A. iridescens, A. melas, A. multicinctus, and A. paucidens). Atractus boulengerii is rediscovered and redescribed from a specimen from the Colombian coast. The first voucher specimens are reported for A. melas. The current status of A. microrhynchus is maintained based on the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…However, when referring to this work to compare previously unexamined material from Ecuador, it became clear to us that several Ecuadorian specimens of Pacific lowland Atractus could not be assigned to any taxa currently recognized to occur in the country. Some specimens identified as Atractus medusa (Passos et al 2009a) matched the coloration of the first specimen reported in Ecuador by Cisneros-Heredia and Romero (2015), but they did not match the coloration of the holotype (Passos et al 2009a). Other specimens were closer in coloration and lepidosis to Atractus iridescens (Peracca, 1860) from Colombia, and others resembled both Atractus microrhynchus (Cope, 1868) and Atractus occidentalis (Savage, 1955).…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…However, when referring to this work to compare previously unexamined material from Ecuador, it became clear to us that several Ecuadorian specimens of Pacific lowland Atractus could not be assigned to any taxa currently recognized to occur in the country. Some specimens identified as Atractus medusa (Passos et al 2009a) matched the coloration of the first specimen reported in Ecuador by Cisneros-Heredia and Romero (2015), but they did not match the coloration of the holotype (Passos et al 2009a). Other specimens were closer in coloration and lepidosis to Atractus iridescens (Peracca, 1860) from Colombia, and others resembled both Atractus microrhynchus (Cope, 1868) and Atractus occidentalis (Savage, 1955).…”
Section: Introductionmentioning
confidence: 64%
“…The remaining individuals were detected by turning over logs, rocks and other surface objects. All specimens included in the genetic analyses were morphologically identified according to Savage (1955, 1960), Cisneros-Heredia (2005), Passos et al (2009a), Arteaga et al (2013), Schargel et al (2013) and Salazar-Valenzuela et al (2014). We generated sequence data for samples marked with an asterisk under Appendix I, which includes museum vouchers at the Museo de Zoología de la Universidad Tecnológica Indoamérica (MZUTI), the División de Herpetología del Museo Ecuatoriano de Ciencias Naturales (DHMECN) and the Fundación Herpetológica Gustavo Orcés (FHGO).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations